Overexpression of fatty acid synthase attenuates bleomycin induced lung fibrosis by restoring mitochondrial dysfunction in mice - Hyesun Shin; Shinhee Park; Jisu Hong; Ae-Rin Baek; Junehyuk Lee; Do-Jin Kim; An-Soo Jang; Su Sie Chin; Sung Hwan Jeong; Sung-Woo Park (Scientific Reports, 2023)
Abstract Proper lipid metabolism is crucial to maintain alveolar epithelial cell (AEC) function, and excessive AEC death plays a role in the pathogenesis of idiopathic pulmonary fibrosis (IPF). The mRNA expression of fatty acid synthase (FASN), a key enzyme in the production of palmitate and other fatty acids, is downregulated in the lungs of IPF patients. However, the precise role of FASN in IPF and its mechanism of action remain unclear. In this study, we showed that FASN expression is significantly reduced in the lungs of IPF patients and bleomycin (BLM)-treated mice. Overexpression of FASN significantly inhibited BLM-induced AEC death, which was significantly potentiated by FASN knockdown. Moreover, FASN overexpression reduced BLM-induced loss of mitochondrial membrane potential and the production of mitochondrial reactive oxygen species (ROS). Oleic acid, a fatty acid component increased by FASN overexpression, inhibited BLM-induced cell death in primary murine AECs and rescue BLM induced mouse lung injury/fibrosis. FASN transgenic mice exposed to BLM exhibited attenuated lung inflammation and collagen deposition compared to controls. Our findings suggest that defects in FASN production may be associated with the pathogenesis of IPF, especially mitochondrial dysfunction, and augmentation of FASN in the lung may have therapeutic potential in preventing lung fibrosis.